Efeito do grau de cristalinidade da sílica na reatividade de agregados em ambiente alcalino - Lima, Mayanny Rodrigues de Morais (2016)
Among several pathological manifestations, alkali-aggregate reaction can be considered as one of the most aggressive concrete degradation processes. This phenomenon can be defined as a deleterious chemical process resulting from the interaction between the reactive silica present in the aggregate (rocks) and the alkalis (Na2O and K2O) generally from cement. Reaction can be classified in three categories: alkali-silicate reaction, álcali-carbonate and alkali-silica. As a result of this interaction (alkali-silica), an amorphous silicon-alkaline gel is originated, which in the presence of water molecules, it becomes expansive, leading to cracks in the concrete structure, affecting negatively in the strength and durability of concrete. Assuming that the type of aggregate, especially the one from the little crystallized structures are more susceptible for the formation of RAA products, this study aims to determine the degree of crystallinity of some aggregates from crystalline sources and analyze its behavior correlating with the reactivity by x-ray florencence tests, x-ray diffraction, infrared spectroscopy and scanning electron microscopy, when aggregates are subjected to different molarity and temperature conditions and type of álcali. The results obtained in this research showed, through XRF analyzes, higher alkali contents for crushed stone 2 (lower degree of crystallinity). The X-ray diffraction (XRD) analyses showed formation of new crystalline phases and possible potentialities of the albite and biotite minerals for the formation of alkali-silica gels due to the decrease of their peak intensities. In the IR, Si-O band enlargement was observed, demonstrating disorder of its structure due to attack of alkaline hydroxides. It was also observed through the scanning electron microscopy analysis (SEM), degradations and deposits on the grains surfaces showing the formation of alkalisilica gels.